Paucibacillary case of Hansen’s disease affecting the skin and nasal mucosa (Brazilian Journal of Health Research, 2024)
Introduction: Hansen’s disease is an infectious disease caused by Mycobacterium leprae. Nasal mucosa is the main entry point and initial site of lesions. Nasal symptoms are uncommon in paucibacillary forms. Case report: Man, 72 years old, presented with erythematous-violaceous infiltrated patches on the back and buttocks for 1 year and 6 months, associated with nasal obstruction, rhinorrhea, and episodes of epistaxis in the right nostril. Rhinoscopy revealed septal bulging to the right and infiltrative lesions. Granulomatous inflammation observed in the nasal mucosa histopathology supported the diagnosis of leprosy tuberculoid borderline with nasal involvement. Conclusion: Nasal cavity examination aids in diagnosing early forms of leprosy. Hansen’s disease rhinitis should be suspected in the presence of chronic nasal obstruction, epistaxis, crusting, and rhinorrhea.
Keywords: Hansen; Rhinorrhea; Epistaxis